Pemetaan Tren Penelitian Penerjemahan dan Penjurubahasaan di Indonesia (2020-2024) - Bety Mawarni (Jurnal Penerjemahan, 2026)
This study maps the emerging themes and methodological approaches characterizing translation and interpreting (T&I) research published by Indonesian-affiliated authors between 2020 and 2024. A systematic mapping review design was adopted, drawing on Grant and Booth (2009) and Cooper (2016), with data collected from Google Scholar via Publish or Perish and GARUDA using bilingual keyword clusters. Following systematic screening of 1,453 deduplicated records, 753 publications were included in the final corpus. Findings reveal four dominant thematic clusters: machine translation quality evaluation, audiovisual translation, translation techniques and strategies, and cultural and literary translation. Interpreting studies account for less than 9% of the corpus, reflecting not merely a research gap but an institutional failure to nurture interpreting as a distinct academic and professional discipline in Indonesia. Qualitative textual analysis dominates methodologically, with an emerging computational strand concentrated in internationally indexed outlets. The study provides a preliminary baseline map of accessible Indonesian T&I journal literature, with implications for researchers, educators, professional bodies, and policy makers seeking to strengthen the field’s scholarly infrastructure.This study maps the emerging themes and methodological approaches characterizing translation and interpreting (T&I) research published by Indonesian-affiliated authors between 2020 and 2024. A systematic mapping review design was adopted, drawing on Grant and Booth (2009) and Cooper (2016), with data collected from Google Scholar via Publish or Perish and GARUDA using bilingual keyword clusters. Following systematic screening of 1,453 deduplicated records, 753 publications were included in the final corpus. Findings reveal four dominant thematic clusters: machine translation quality evaluation, audiovisual translation, translation techniques and strategies, and cultural and literary translation. Interpreting studies account for less than 9% of the corpus, reflecting not merely a research gap but an institutional failure to nurture interpreting as a distinct academic and professional discipline in Indonesia. Qualitative textual analysis dominates methodologically, with an emerging computational strand concentrated in internationally indexed outlets. The study provides a preliminary baseline map of accessible Indonesian T&I journal literature, with implications for researchers, educators, professional bodies, and policy makers seeking to strengthen the field’s scholarly infrastructure.